Relevansi Prinsip Efisiensi Dan Distribusi Fiskal Abu Yusuf Dalam Kebijakan Fiskal Indonesia: Analisis Komparatif Terhadap Era Purbaya Yudhi Sadewa - Hanum, Fathmah; Yazid, Muhammad; Musfiqoh, Siti; Bakhri, Saiful (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study analyzes the relevance of Abu Yusuf's fiscal thought in the context of contemporary Indonesian fiscal policy, particularly during Purbaya Yudhi Sadewa's tenure as Minister of Finance. Indonesia faces a budgetary dilemma between spending efficiency and equitable distribution of fiscal burdens. Through Kitab al-Kharaj, Abu Yusuf offers a conceptual framework that balances economic efficiency with social justice in public financial management. This research employs a qualitative method with a library research approach, analyzing primary sources including Kitab al-Kharaj and secondary sources comprising policy documents and academic literature. Analysis is conducted comparatively-descriptively through three stages: concept identification, principle comparison, and relevance evaluation. Findings reveal fundamental alignment between Abu Yusuf's principles and Purbaya's policies regarding budget allocation efficiency, subsidy control, and welfare orientation. Both approaches emphasize transparency, accountability, and proportionality in state financial management. However, implementing Abu Yusuf's principles in Indonesia still faces structural challenges including inter-regional fiscal distribution inequality, weak accountability enforcement, and minimal ethical dimensions in fiscal policy. This study recommends integrating classical Islamic economic values into Indonesian fiscal policy formulation to strengthen moral foundations and social justice.